Analysis of Education Level and Unemployment on Poverty Rates in Nias Islands 2013-2023 - Deyren Firmansyah; Muammar Rinaldi; Marshanda Hutagalung; M. Abdan Syahkura Anuradi; Venus Situmeang (Outline Publisher, 2025)
This study aims to analyze the relationship between education level, open poverty level, and poverty in Nias Regency during the period 2013–2023. Nias Regency still faces major challenges in economic and social development, relatively low levels of community education, declining unemployment rates, and poverty lines that tend to increase from year to year. Based on BPS data and various recent scientific literature, it was found that improvements in education have not significantly reduced poverty rates. Expert opinions such as Zebua and Laoli (2023) state that low workforce skills are the main cause of high poverty rates. Meanwhile, Latif and Ramadhani (2024) emphasize the importance of investing in education in reducing poverty rates sustainably. This study uses a quantitative descriptive approach with secondary data analysis to determine the pattern of relationships between variables. The results of the analysis are expected to be used as consideration in the preparation of regional policies that focus on strengthening the quality of human resources as a strategy for overcoming poverty in Nias Regency.